Impact of board characteristics on the adoption of sustainable reporting practices - Bashar Abukhalaf (21488780) (2024)
This study examines the influence of board characteristics on company’s sustainability reporting in the GCC region. In contrast to prior research, we investigate the relationship between variables across a span of eleven years, encompassing all nonfinancial firms listed on the GCC stock exchanges. Our study addresses the scarcity of research undertaken in the GCC region on this particular topic. This study empirically investigates the relationship between board characteristics (specifically, board size, board gender diversity, board meetings, and board independence) on the adoption of sustainable reporting while taking into account firm characteristics (including leverage, profitability, liquidity, and firm size) and controlling for macroeconomic variables (such as GDP and inflation). This research utilized Probit regression to examine the influence of the likelihood of various variables on the adoption of sustainable reporting. The findings indicated that larger board sizes, a higher proportion of female board members, the inclusion of more independent directors, and more frequent board meetings all contribute to the improvement of sustainable reporting. Furthermore, the greater the size, the greater is the impact of profitability and liquidity on the sustainability of reporting. The current research offers some insights into the connection between board characteristics and corporate sustainability reporting for corporate boards, regulators, and practitioners who are interested in promoting sustainable reporting. Further investigation should examine the comparison of sustainability reporting methodologies across different regions, as well as between privately held and publicly listed corporations. Finally, as evident by the results reported in the Maximum Likelihood Estimator our results are robust. Other Information Published in: Cogent Business & Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23311975.2024.2391563